Review on Air Cathode in Li-Air Batteries - Zha, Zhaoru; Shen, Cai; Wang, Deyu; Han, Weiqiang (Journal of Technology Innovations in Renewable Energy, 2013)
Lithium-air (Li-air) battery is a promising electrochemical system with unprecedented high energy density. However, many problems and challenges prevent its wide scale application and commercialization. Low oxygen diffusion rates and large voltage gap are two of the main problems in Li-air battery. These two problems are related to the materials used in the air cathode such as porous carbon materials and metallic catalysts. This review seeks to discuss various materials used in the air cathode for Li air batteries. Mechanism of reaction in air cathode will be elucidated and discussed.